A switching LOS guidance with relative kinematics for path-following of underactuated underwater vehicles - Abdurahman, Bilal; Savvaris, Al; Tsourdos, Antonios (Elsevier, 2017)
This paper presents a switching heuristic for the enclosure-based line-of-sight (ELOS) guidance and the concept of relative kinematics. The switching scheme proposed addresses the need for additional path-approaching strategies required in ELOS guidance in case of large cross-track errors. A nonlinear controller is applied to solve the path-following problem as a maneuvering problem, and the resulting guidance system with the relative kinematics perform well in compensating for drift caused by strong ocean currents. Stability and convergence analysis of the closed-loop systems are also provided along with simulation results showing straight-line waypoint-following performance of an AUV.
Keywords: line-of-sight guidance; current compensation; underwater vehicles; AUVs; path-following control